Pendidikan kesehatan tentang toilet training melalui audio visual terhadap pengetahuan ibu - Marliyana Marliyana; Dian Mentari Putri; Sri Suharti (THE JOURNAL OF Mother and Child Health Concerns, 2024)
Background: According to the national household health survey (SKRT), there are 75 million children in the toddler to preschool age who have difficulty controlling defecation and urination. One way to increase knowledge and change behavior is health education. Toilet training is an important part of child development, parents can teach children to control urination and defecation. Mothers should know how to do toilet training correctly so that their children can do it well. Audio visuals are used to provide information that is easier to receive. Purpose: To determine the application of audio visual health education on maternal knowledge. Method: This type of scientific paper is descriptive. The subjects used were 30 mothers who had children aged 1-3 years at Posyandu Mawar I Bandar Lampung. Results: Before being given health education, the level of maternal knowledge was 17 subjects (56.67%), the level of good knowledge was 13 subjects (43.33%). After being given health education, the level of maternal knowledge was good as many as 26 subjects (86.67%), the level of knowledge was sufficient as many as 4 subjects (13.33%). Conclusion: From the results of the study there was an increase in the percentage of knowledge categories from 43.33% to 86.67%. Keywords: Health Education; Knowledge; Toilet Training. Pendahuluan: Menurut survei kesehatan rumah tangga (SKRT) nasional, ada 75 juta anak di usia toddler hingga prasekolah yang mengalami kesulitan mengontrol BAB dan BAK. Salah satu cara untuk meningkatkan pengetahuan dan mengubah perilaku masyarakat adalah pendidikan kesehatan. Toilet training merupakan hal penting perkembangan anak, orang tua dapat mengajarkan anak-anak mengendalikan buang air kecil dan buang air besar. Ibu harus tahu bagaimana melakukan pelatihan toilet dengan benar agar anak-anaknya mampu melakukannya dengan baik. Audio visual digunakan untuk menyediakan informasi yang lebih mudah diterima. Tujuan: Untuk mengetahui penerapan pendidikan kesehatan audio visual terhadap pengetahuan ibu. Metode: Jenis karya tulis ilmiah ini adalah deskriptif. Subjek yang digunakan adalah 30 ibu yang mempunyai anak usia 1-3 tahun di Posyandu Mawar I Bandar Lampung. Hasil: Sebelum diberikan pendidikan kesehatan tingkat pengetahuan ibu cukup terdapat 17 subjek (56.67%), tingkat pengetahuan baik sebanyak 13 subjek (43.33%). Setelah diberikan pendidikan kesehatan tingkat pengetahuan ibu baik sebanyak 26 subjek (86.67%), tingkat pengetahuan cukup sebanyak 4 subjek (13.33%). Simpulan: Dari hasil penelitian terjadi peningkatan presentase kategori pengetahuan dari 43.33% menjadi 86.67%. Kata Kunci: Pendidikan Kesehatan; Pengetahuan; Toilet Training.